Modelling of User Perspective of M-Government Adoption Preferences Constructs - Mohammed Alneyadi, Rashed Hamad Rashed; Hamid, Nor Aziati Abdul (International Journal of Sustainable Construction Engineering and Technology, 2022)
Mobile government system has got a worldwide attention including the United Arab Emirates (UAE) government. The government is promoting the adoption of M-government services resulted from several hinderence such as trust on e-services and culture. People can be motivated to adopt this current trend through understanding the preferences. Hence, this paper presents the development of six constructs models having 30 preferences of adopting M-government services from the perception of the UAE people. The constructs are Social Influence (SI), Perceived Compatibility (PC), Perceived Ease of Use (PEOU), Perceived Usefulness (PU), Trust in Technology (TT) and Perceived Risk (PR). These constructs were modelled using AMOS software with 263 samples collected data from people of the UAE. It was found that all the constructs achieved the fitness values which indicates there is strong relationship amongst the measuring preferences for adopting the M-government services for the people of UAE. These findings of the study will help devise strategies to promote M-government services in the UAE.